2016
DOI: 10.1371/journal.pone.0157919
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in Healthy Individuals Results in Increased Mixed Cytokine Profiles, Altered Neutrophil Subsets and Function

Abstract: Malnutrition is commonly associated with increased infectious disease susceptibility and severity. Whereas malnutrition might enhance the incidence of disease as well as its severity, active infection can in turn exacerbate malnutrition. Therefore, in a malnourished individual suffering from a severe infection, it is not possible to determine the contribution of the pre-existing malnutrition and/or the infection itself to increased disease severity. In the current study we focussed on two groups of malnourishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 44 publications
(56 reference statements)
3
31
0
2
Order By: Relevance
“…Further evidence of the relationship of malnutrition with inflammation is the study by Takele et al who found a significant correlation between low BMI and increased levels of IFN-γ, IL-2, IL-12, IL-4, IL-5, IL-13, IL-10, IL-33, and TNFα; however, not IL-8 or CRP. Their results show that even in the absence of apparent infections, healthy malnourished individuals display dysfunctional immune responses which may cause increased susceptibility to infectious diseases with more severe presentations [40].…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence of the relationship of malnutrition with inflammation is the study by Takele et al who found a significant correlation between low BMI and increased levels of IFN-γ, IL-2, IL-12, IL-4, IL-5, IL-13, IL-10, IL-33, and TNFα; however, not IL-8 or CRP. Their results show that even in the absence of apparent infections, healthy malnourished individuals display dysfunctional immune responses which may cause increased susceptibility to infectious diseases with more severe presentations [40].…”
Section: Discussionmentioning
confidence: 99%
“…Both malnutrition and infection are linked. Malnutrition in healthy individuals with a low body-mass index can increase the expression levels of various cytokines (Takele et al, 2016). Both pregnancy and lactating states are energetically the costliest (Scantlebury et al, 2000;Kastelein et al, 2002) and therefore requires increased food intake (East et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although neutrophil capacity to phagocytose is not impaired, the capacity to produce reactive oxygen species is impaired. It was suggested that these dysfunctional immune responses displayed in healthy severely malnourished individuals might contribute to increased susceptibility to infectious diseases (Takele et al., ). This suggestion is supported by the present finding that despite guava consumption this subject developed 48% BGS.…”
Section: Discussionmentioning
confidence: 99%